Nodes and networks in diachronic construction grammar - Sommerer, Lotte; Smirnova, Elena (Constructional approaches to language ;, 2020)
"This volume brings together ten contributions by leading experts who present their current usage-based research in Diachronic Construction Grammar. All papers contribute to the discussion of how to conceptualize constructional networks best and how to model changes in the constructicon, as for example node creation or loss, node-external reconfiguration of the network or in/decrease in productivity and schematicity. The authors discuss the theoretical status of allostructions, homostructions, constructional families and constructional paradigms. The terminological distinction between constructionalization and constructional change is revisited. It is shown how constructional competition but also general cognitive abilities like analogical thinking and schematization relate to the structure and reorganization of the constructional network. Most contributions focus on the nature of vertical and horizontal links. Finally, it is also being discussed how existing network models should be enriched or reconceptualized in order to integrate theoretical, psychological and neurological aspects missing so far"--